A case report of isolated right ventricular lymphocytic myocarditis - Indraratna, Praveen (Eur Heart J Case Rep, 2020)
BACKGROUND: Lymphocytic myocarditis is an uncommon condition with a variety of clinical presentations. Isolated involvement of the right ventricle (RV) is very rare. We present a case of a young woman who developed right ventricular dysfunction and arrhythmias as a consequence of this condition, which appeared to be chronic at diagnosis. CASE SUMMARY: A 26-year-old lady was admitted to hospital following routine echocardiography, requested for screening of pulmonary hypertension in the context of known hypersensitivity pneumonitis. This echocardiogram demonstrated severe right ventricular dilatation and impairment. She was also experiencing atrial fibrillation and non-sustained, symptomatic episodes of ventricular tachycardia. Endomyocardial biopsy revealed lymphocytic myocarditis. She was managed with azathioprine and prednisone, as well as sotalol and apixaban for her atrial fibrillation, and has had no complications in the 12 months since discharge. DISCUSSION: Lymphocytic myocarditis isolated to the RV has only been reported in two previous cases, both of which were acute, dramatic presentations. This is the first report of a chronic example of this disease process. Due to her intercurrent immunosuppression, this patient may have been pre-disposed to the condition either by re-activation of a latent viral infection or partial treatment of a true autoimmune lymphocytic myocarditis.